Impulsive mean square exponential synchronization of stochastic dynamical networks with hybrid time-varying delays - Wang, Fei; Yang, Yongqing (Nonlinear Analysis: Modelling and Control, 2018)
This paper investigates the mean square exponential synchronization problem for complex dynamical networks with stochastic disturbances and hybrid time-varying delays, both internal delay and coupling delay are considered in the model. At the same time, the coupled time-delay is also probabilistic in two time interval. Impulsive control method is applied to force all nodes synchronize to a chaotic orbit, and impulsive input delay is also taken into account. Based on the theory of stochastic differential equation, an impulsive differential inequality and some analysis techniques, several simple and useful criteria are derived to ensure mean square exponential synchronization of the stochastic dynamical networks. Furthermore, pinning impulsive strategy is studied. An effective method is introduced to select the controlled nodes at each impulsive constants. Numerical simulations are exploited to demonstrate the effectiveness of the theory results in this paper.
Keywords: stochastic dynamical networks; hybrid time-delay; impulsive input delay; probabilistic time-delay